Ecological status interactions for assessing bird diversity in relation to a heterogeneous landscape structure. (1st March 2013) - Bensizerara, Djamel; Chenchouni, Haroun; Bachir, Abdelkrim Si; Houhamdi, Moussa
Avian diversity is used to assess the functionality of diverse types of habitats around Salt Lake Djendli, Northeast Algeria. The landscape is stratified into five habitat types in a gradient from wetland to forested mountains. Bird species found in these habitats can be classified into four ecological groups with decreasing degrees of aquatic specialisation and increasing forest specialisation. For each surveyed species, five ecological status were assigned. Overall, there was lower species richness in urban areas compared to other "natural" habitats. Birds have a biogeographical affinity to the western Palaearctic according to the dominant faunal types. Interactions of ecological status with phenological traits reveal that water birds are different from non-aquatic species because most of them are migrants. Moreover, overall, there is no worrying conservation status for surveyed birds. Bird diet is dependent on the ecological status that differentiate bird groups from each other due to differences in the food resources of the habitats they frequent. Phenological categories tend to link together birds of urban and open-lands. These two groups are affected by seasonal human activities. Our findings emphasise the importance of using combinations within the birds' ecological status, which would give information on the actual state of avifauna. This approach is relevant for future programmes and conservation actions.